2009
DOI: 10.1029/2008gb003406
|View full text |Cite
|
Sign up to set email alerts
|

Shelf‐derived iron inputs drive biological productivity in the southern Drake Passage

Abstract: In the Southern Ocean near the Antarctic Peninsula, Antarctic Circumpolar Current (ACC) fronts interact with shelf waters facilitating lateral transport of shelf‐derived components such as iron into high‐nutrient offshore regions. To trace these shelf‐derived components and estimate lateral mixing rates of shelf water, we used naturally occurring radium isotopes. Short‐lived radium isotopes were used to quantify the rates of shelf water entrainment while Fe/228Ra ratios were used to calculate the Fe flux. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
108
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 122 publications
(115 citation statements)
references
References 67 publications
(76 reference statements)
7
108
0
Order By: Relevance
“…The radium activities reported in this study are shown in Table 1 and fall in the range of previous radium data reported for surface waters near islands of the Southern Ocean (Annett et al, 2013;Charette et al, 2007;Dulaiova et al, 2009;Hanfland, 2002;Kaufman et al, 1973;Sanial et al, 2014;van Beek et al, 2008). The highest 223 Ra, 224 Ra and 228 Ra activities are found in seawater samples collected at shallow stations near the Kerguelen Islands (bathymetry < 200 m; Fig.…”
Section: Radium Distribution In Surface Waterssupporting
confidence: 56%
See 1 more Smart Citation
“…The radium activities reported in this study are shown in Table 1 and fall in the range of previous radium data reported for surface waters near islands of the Southern Ocean (Annett et al, 2013;Charette et al, 2007;Dulaiova et al, 2009;Hanfland, 2002;Kaufman et al, 1973;Sanial et al, 2014;van Beek et al, 2008). The highest 223 Ra, 224 Ra and 228 Ra activities are found in seawater samples collected at shallow stations near the Kerguelen Islands (bathymetry < 200 m; Fig.…”
Section: Radium Distribution In Surface Waterssupporting
confidence: 56%
“…The KEOPS-2 cruise was conducted during austral spring 2011 to the east of the Kerguelen Islands. Natural radio-tracers such as radium isotopes ( 223 Ra, T 1/2 = 11.4 d; 224 Ra, T 1/2 = 3.66 d; 228 Ra, T 1/2 = 5.75 yr) have already been proved to be powerful tools to track the origin and fate of chemical elements -including iron and other micronutrients -which are released by the sediments deposited on the shelves (Annett et al, 2013;van Beek et al, 2008;Charette et al, 2007;Dulaiova et al, 2009;Sanial et al, 2014). In this work, we refer to these latter inputs as "sediment-derived inputs".…”
Section: Sanial Et Al: Use Of Ra Isotopes To Deduce Rapid Transfementioning
confidence: 99%
“…In contrast, when the main current flows parallel to the shelf, export from the coastal system into the open ocean would be less effective. Previous studies in our sampling area also demonstrated that lateral transport in transects from the coast to Drake Passage (perpendicular to the main currents) was not as efficient as that in the Bransfield Strait-Elephant Island sections (Dulaiova et al, 2009). To estimate how effective the coastal inputs are for long-range bio-available iron transport, including northward transport by the slower meridional flow (Cassar et al, 2008), we calculated "scale length" of the DFe and TaLFe concentrations from the coastal survey data in two transects which were perpendicular to the coastal currents to the northwest of Livingston Island (see Fig.…”
Section: Scale Lengths Of Fe Transportmentioning
confidence: 76%
“…This remobilized Fe can also be transported to offshore regions through lateral water mixing. Previous studies (Dulaiova et al 2009;Ardelan et al 2010) showed that the transport of the Antarctic shelf-water to the Southern Ocean is an important mechanism for Fe delivery to the offshore region. For example, Dulaiova et al (2009) reported that the Fe flux through lateral transport to the Drake Passage is 4.0 )10 7 mol Fe yr (1 , which is much larger than the vertical flux of dust-borne Fe.…”
Section: Implication: Gmw As a Source Of Fe In The Southern Oceanmentioning
confidence: 99%
“…Previous studies (Dulaiova et al 2009;Ardelan et al 2010) showed that the transport of the Antarctic shelf-water to the Southern Ocean is an important mechanism for Fe delivery to the offshore region. For example, Dulaiova et al (2009) reported that the Fe flux through lateral transport to the Drake Passage is 4.0 )10 7 mol Fe yr (1 , which is much larger than the vertical flux of dust-borne Fe. Ardelan et al (2010) also suggested that this supply of Fe by lateral transport contributes significantly to high phytoplankton biomass in the Scotia Sea region.…”
Section: Implication: Gmw As a Source Of Fe In The Southern Oceanmentioning
confidence: 99%